Estimasi Biaya Software FAS (Financing Analysis System) Menggunakan Metode Function Point (Studi Kasus Pada PT BPRS Lantabur Tebuireng) - Juliana Kristi; Siti Nur Aisah; Renny Sari Dewi (JURIKOM (Jurnal Riset Komputer), 2020)
Software cost estimation is the process of predicting software development efforts. The basic input of software cost estimation is the measurement metric. Projects often experience delays, over-budget, and are not completed due to failure to estimate software development costs. PT BPRS (Bank Perkreditan Rakyat Syariah) Lanatabur Tebuireng determines the estimated cost based on the amount of human resources, features needed, and funds owned. This study explains the estimated costs of the FAS (Financing Analysis System) software at PT BPRS Lantabur Tebuireng using the Function Point method. Function Point is a method of measuring software functionality based on the type of user function that is External Input, External Output, External Inquire, Internal Logic File, and External Interface File as well as technical calculations of software development. The final of the FAS (Financing Analysis System) study cost around IDR 94,797,120.